Origin of Cave Fungi - Zhang, Zhi-Feng; Zhao, Peng; Cai, Lei (Frontiers in Microbiology, 2018)
Karst caves are obviously characterised by darkness, constantly low temperature, high humidity, and oligotrophy. Previous studies revealed that Karst caves have a high and specific bio-diversity. A large number of troglobiont animals had been discovered and their evolution and speciation have been well investigated. However the origin and evolution of cave fungi remain unknown. In previous study, we have identified 20 new species, which accounted for 49 % of the total number of new species of fungi ever described from caves. In this study, we inferred the divergence times of these 20 new species, and compared to the cave formation geologic age. The fossil-calibrated molecular clock showed that the divergence time of these 20 suspected troglobitic fungi are between late Miocene (7.2 Mya for Metapochonia variabilis) and late Jurassic (158 Mya for Gymnoascus exasperates). While based on the historical geological movement and the paleoclimate of Guizhou, it has been estimated that the development of caves in this area were later than middle Pliocene (3.5 – 4 Mya). It is therefore concluded that the new species described from these cave are unlikely troglobitic fungi but travelers from other environments. The geographic history of cave appeared to be too short for fungal speciation.